‘We have beaten HIV a bit’: a qualitative study of experiences of peer support during pregnancy with an HIV Mentor Mother project in England - Redshaw, M; McLeish, J (BMJ Publishing Group, 2016)
Objectives: To explore the experiences of women living with HIV in England who received or gave Mentor Mother (trained mother-to-mother) volunteer peer support during pregnancy and early motherhood. Design: Qualitative descriptive study, using semi-structured, in-depth interviews and inductive thematic analysis, theoretically informed by phenomenological social psychology. Setting: A London-based third sector peer support organisation for people living with HIV. Participants: 12 women living with HIV who had given or received Mentor Mother volunteer peer support (6 had given support and 6 had received support). 11 were Black African. Results: The key themes in participants’ descriptions of their lives as pregnant women and mothers living with HIV were ‘fear and distress’, ‘stigma and isolation’, and ‘the gap in maternity care’. The key themes related to Mentor Mother peer support during and after pregnancy were ‘support to avoid mother-to-child transmission’ (with sub-themes ‘reinforcing medical advice’, ‘reframing faith issues’, ‘prioritisation and problem-solving’, and ‘practical strategies for managing HIV and motherhood’), and ‘emotional support’ (with sub-themes ‘role modelling and inspiring hope’, ‘openness and non-judgemental acceptance’, ‘a caring relationship’, ‘recreating the lost family network’, ‘being understood from the inside’ and ‘self-confidence’). The Mentor Mothers’ support appeared to be a successful hybrid between the peer education Mentor Mothers programmes in southern Africa and the more general pregnancy volunteer peer support models operating in England. Conclusions: A Mentor Mother peer support programme is acceptable to, and valued by, Black African mothers with HIV in England. Peer support from trained volunteers during and after pregnancy can complement and reinforce medical advice on avoiding mother-to-child transmission of HIV, and can have a multi-dimensional positive impact on vulnerable mothers’ emotional wellbeing. Mentor Mother peer support should be considered by those designing programmes for the support of pregnant women with HIV and the prevention of mother-to-child transmission of HIV.